The Influence of Convection Heat Transfers for Vertical Mini-Tubes Using Solvent Carbon Dioxide and Porous Media at Supercritical Pressure - Bilal Kkihlefa; Ameer Jaddoa; Ahmed Reja (Engineering and Technology Journal, 2021)
Porous media and solvent CO2 at supercritical pressure were investigated experimentally to study the effect of convection heat transfer in vertical mini-tubes. Mini-tubes diameter (5 and 8 mm) with medium porosity of 0.5 are proposed in experimental investigation. Experimental conditions consisted of bulk fluid, wall temperatures ranged from 33 to 55 oC, and 8 to 10 MPa of pressure. Reynolds number, Mass flow rate, and heat flux were 1750 to 21000, 0.5 to 4.5 Kg/h, and 3.25×104 to 1.1×105 W/m2 respectively. Some chemical additives like Ethanol, Chloroform, Acetone, Dimethyl sulfoxide, and Methanol were considered. A special focus was dedicated to studying the influence of heat flux, inlet temperature, and mass flow rate at measured values of wall and fluid bulk temperatures, and coefficients of local heat transfer for mini-tubes and porous media. A higher effect was noticed on the convection heat transfer by buoyancy and properties of the thermophysical variable of solvent CO2 in mini-tube at vertical position. However, when these results were compared with the controls (empty tube) shoewn dramatically different results. Heat transfer coefficient was bigger about 4 times when using the porous media tube compared with the empty type in the case of using a 5% of acetone solvent.